Detailed feasibility study of the pre-cast reinforced concrete project and its importance in the construction of Iraq - Mohammed, Mohammed Jasim; Mahmood, Zinah Muayad (Journal of Economics and Administrative Sciences, 2021)
Purpose: Providing practical knowledge of the requirements of a detailed feasibility study for selecting the investment project. Findings: Directing the private sector towards investing in productive projects - the pre-cast reinforced concrete project - as it achieves a financial return as well as providing Providing foreign currencies by reducing imports and exploiting available natural resources Practical implications: The importance of a detailed feasibility study to determining whether the project can be implemented or not. The precast concrete method is one of the best modern construction methods (high quality, low cost and fast to implement). Social implications: Rapid treatment of destroyed infrastructure, consequently restoring stability to liberated areas, and community reconstruction. Providing additional job opportunities that are sustainable, which contributes to reducing unemployment. And Reducing environmental pollutants. Originality/value: The research has the value of originality, as it deals with the details of an industrial project in several aspects (technical, legal, environmental and economic impacts). Abstract The feasibility study for the investor of the project is considered as the guide that illuminates a path towards safe investment, as it cares about the investment opportunity and reaching the final decision to accept the opportunity and convert it from just an idea to a project or reject it. As a result of the increasing need in Iraq to complete the construction work of the service sector (health, education and housing) in addition to reconstructing the provinces that were exposed to military operations, it was necessary to find alternatives that are characterized by low costs and fast delivery, also to finding solutions to the problem of government’s inability to finance investment projects. Therefore, it was suggested that the private sector invests in a Pre-cast project to solve this problem. The project site chosen in Anbar Governorate / Fallujah district because the site has several advantages, the most important one is the availability of raw materials, Also the roads connecting the province to the nearby governorates. The total area of ​​the project is (23,200)m2 and consists of a line for production roofs with a capacity of 650 m 3/ day and a line for production walls with a capacity of 1000 m 3/ day. The expected duration of completing the project is one year and the productive life of the project is ten years. On the basis of the expected demand, the expenses and revenues were estimated and analyzed to reach an evaluation of the project’s economic feasibility, where the expected internal rate of return for the project (IRR) (38%) and the recovery period is two years and 4 months.